Selling Strategic Information in Digital Competitive Markets - David Bounie; Antoine Dubus; Patrick Waelbroeck (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper investigates the strategies of a data broker in selling information to one or to two competing firms that can price-discriminate consumers. The data broker can strategically choose any segment of the consumer demand (information structure) to sell to firms that implement third-degree price-discrimination. We show that the equilibrium profits of the data broker are maximized when (1) information identifies the consumers with the highest willingness to pay; (2) consumers with a low willingness to pay remain unidentified; (3) the data broker sells two symmetrical information structures. The data broker therefore strategically sells partial information on consumers in order to soften competition between firms. Extending the baseline model, we prove that these results hold under first-degree price-discrimination.
Keywords: D40; D80; L50; D43; 330; data broker; information structure; price-discrimination